Permeability modelling of polymer-layered silicate nanocomposites - Lu, Chunsheng; Mai, Y. (Elsevier Ltd, 2007)
With the addition of very low loading of exfoliated silicate fillers, the permeability of polymer-layered silicate nanocomposites remarkably decreases. In the paper, based on comparisons between experimental results and expectations of several existing models, we propose an improved tortuosity-based model, in which the random motion of gas/liquid molecules in a constrained environment is considered. We show that the pathway of a diffusing gas/liquid molecule in exfoliated polymer-layered silicate nanocomposites is akin to a self-avoiding random walk. The estimated critical volume fractions of clay fillers for the minimum permeability, in terms of the concept of renormalization, concur with available experimental data.